Confucian culture and competition law in East Asia - Ma, Jingyuan; Marquis, Mel (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
Competition law is a significant legal transplant in East Asia, where it has come into contact with deeply rooted variants of Confucian culture. This timely volume analyses cultural factors in mainland China, Japan and Korea, focusing on their shared but diversely evolved Confucian heritage. These factors distinguish the competition law systems of these countries from those of major western jurisdictions, in terms of the goals served by the law, the way enforcement is structured, and the way subjects of the law respond to it. Concepts from cultural studies inform a new and eclectic perspective on these dynamics, with the authors also drawing on ideas from law and economics, comparative law, East Asian studies, political science, business management and ethics, and institutional economics. The volume presents a model for cultural analysis of comparative legal topics and contributes to a greater understanding of the challenges to deeper convergence of competition laws between East and West.
Confucian culture and its influence in East Asia -- Confucian business culture and its implications for competition law -- Confucian corporate culture and competition compliance -- Confucian political-bureaucratic culture and its links with the administrative enforcement of competition law -- Confucian 'litigation culture' and the under-development of private antitrust enforcement -- East Asian legal culture and the regional response to the criminalization of cartel conduct.
Title from publisher's bibliographic system (viewed on 02 Sep 2022).
Keywords: Antitrust law -- East Asia; Competition, Unfair -- East Asia; Confucianism and law -- East Asia; Philosophy, Confucian -- East Asia